Junctional and extrajunctional glutamate receptor channels in Drosophila embryos and larvae. - Nishikawa, K.I.; Kidokoro, Y. (Journal of Neuroscience, 1995)
Glutamate receptor channels in Drosophila embryos and larvae were examined with the patch-clamp technique in various configurations. In the cell-attached mode, only one type of channel was observed in the extrajunctional region at any stages. The burst duration histogram was fit with three exponentials. The burst duration of long component lengthened with increasing glutamate concentration. In excised outside-out patches the unitary channel current was 7.1 pA at -60 mV and direction of current reversed at zero membrane potential. In contrast, junctional receptor channels had different properties. In the whole-cell configuration, spontaneous synaptic currents with steps on the falling phase were observed. The step amplitudes had two discrete values of 9.4 and 18.5 pA at -60 mV, due to openings of junctional glutamate receptor channels. Synaptic currents changed amplitudes linearly with the membrane potential in the negative potential range but nonlinearly above zero. With 1 mM glutamate in the bath, synaptic currents were no longer observed. Instead, there were single channel events with the current amplitude varying between 8 and 12 pA at -60 mV. Their long burst duration depended on glutamate concentration indicating that they are glutamate receptor channel events. The extrapolated reversal potential of these channel currents was around +12 mV. These junctional receptor channels were strictly localized at the junction. Our findings suggest that the channel conversion mechanism in Drosophila is different from that observed in vertebrates. Further close examination of other intermediate steps during neuromuscular junction formation is needed.